ANALISIS QUALITY CONTROL HASIL PERCETAKAN PADA CV. TEMPOSO EMAS DI SAMARINDA - Fatmawati, Evy (EKONOMIA, 2012)
The problem of this study is whether the printing process in the CV. Temposo Emas has reached the level of sigma process capability.                From the hypothesis, it is suggested that the production process of printing on CV. Temposo Emas has not yet reached the prescribed standards of quality control.                Based on the data that has been obtained, the average number of daily production to 200 copies with the number of defects of 20%, with a total production of 200 copies / day, authors determined a sample of 540, was obtained by the method Slovin. Sampling was carried out for 20 days.                Once the data is obtained, an analysis using the upper control formula and the lower control formula, using control maps p, and the results of the calculations indicate the center line of 0.201, upper line control at 0.43358, and the lower line control is 0, the proportion of errors 0,7 up to 0.33, which means the process is under control because the value of the proportions is still in the range of the upper line control and the lower line control, however, is still in the process capability sigma level, so the hypothesis that the authors propose is acceptable.